2017
DOI: 10.1371/journal.pntd.0006132
|View full text |Cite
|
Sign up to set email alerts
|

4-aminopyridyl-based lead compounds targeting CYP51 prevent spontaneous parasite relapse in a chronic model and improve cardiac pathology in an acute model of Trypanosoma cruzi infection

Abstract: BackgroundChagas disease, caused by the protozoan Trypanosoma cruzi, is the leading cause of heart failure in Latin America. The clinical treatment of Chagas disease is limited to two 60 year-old drugs, nifurtimox and benznidazole, that have variable efficacy against different strains of the parasite and may lead to severe side effects. CYP51 is an enzyme in the sterol biosynthesis pathway that has been exploited for the development of therapeutics for fungal and parasitic infections. In a target-based drug di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…If correct, this suggests that curative drug treatment should have a beneficial outcome in terms of pathology. Several recent reports focused on acute stage murine infections seem to support this ( 29 33 ). With chronic-stage infections the data are less clear-cut ( 34 ), in part because it is difficult to confirm parasitological cure, even with PCR-based methodologies.…”
Section: Introductionmentioning
confidence: 81%
“…If correct, this suggests that curative drug treatment should have a beneficial outcome in terms of pathology. Several recent reports focused on acute stage murine infections seem to support this ( 29 33 ). With chronic-stage infections the data are less clear-cut ( 34 ), in part because it is difficult to confirm parasitological cure, even with PCR-based methodologies.…”
Section: Introductionmentioning
confidence: 81%
“…Other studies employing bioluminescent T. cruzi consistently have demonstrated that the gastrointestinal (GI) tract is a prominent reservoir for luciferase-expressing T. cruzi during the chronic phase, including T. cruzi Colombiana in Swiss Webster mice (46,48,49). Whatever the degree of trafficking of T. cruzi trypomastigotes between the GI tract and skeletal muscle within C57BL/6 mice, our data indicate a strong correlation between the T. cruzi parasite burden within one organ (quadriceps muscle) and the inflammation of that organ.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the central role played by the parasite in disease pathogenesis strongly implies that effective therapy should block or reduce the development of pathology. Evidence supporting this has come from several reports on the beneficial effects of curative treatment of acute stage infections in experimental models [48][49][50][51][52]. Studies, using highly sensitive in vivo imaging, further suggest that the beneficial outcomes, in terms of protection against cardiac pathology, may be lessened if treatment is withheld until chronic stage symptoms develop [53].…”
Section: The Current Status Of Chagas Disease Chemotherapymentioning
confidence: 98%